Desenvolvimento e caracterização de blendas poliméricas biodegradáveis de quitosana e policaprolactona - Gomes, Ana Catarina Damasceno (2017)
In the scope of researches for new materials for food packaging, chitosan (CHI) is known for forming translucent films. However, it presents restricted mechanical resistance, which limits its use as material for the application in food packaging. To overcome this limitation, the use of chitosan with other polymers for forming biodegradable polymeric blends can be a solution that meets sustainability tendencies. In this sense, polycaprolactone (PCL), a biodegradable polyester with mechanical and kinetic degradation properties, suitable for environmental disposal and relatively cheap production process when compared to other aliphatic polyesters, emerges with great use potential. The objective of this work was to develop polymeric blends based on chitosan and polycaprolactone, added with Tween 80 to 18% (wt/wt) in relation to total polymer mass as coupling agent. The concentrations of CHI and PCL were varied, with the proportions of CHI higher than those of PCL, limiting this last to up to 10% (wt/wt) in relation to the polymer mass, due to its higher cost (in relation to chitosan) and the separation of phases in increased concentrations. The production process was casting, and the blends where characterized regarding morphological (Scanning Electron Microscopy - SEM), mechanical (tensile strength and puncture), optic (color and opacity), water resistance (solubility), water vapor permeability (WVP), structural (X-ray diffraction - XRD and Fourier Transform Infrared Spectroscopy - FTIR) and thermal (Thermogravimetric analysis - TGA and Differential Scanning Calorimetry - DSC) properties. During micrographic analysis, the blend revealed structures in the format of microspheres derived from the PCL in the continuous phase of the CHI. The interaction of the amino groups of the chitosan with the carbonyl of the PCL were evident due to the dislocation to greater wave lengths, related to the absorption bands in the infrared region, which can be attributed to the formation of hydrogen bonds. For the tensile strength mechanical properties, the addition of PCL increased ductility and left the film less rigid in relation to the films made of pure CHI, making them more resilient, that is, capable of absorbing energy within an elastic limit. The quantity of PCL used in the blends was insufficient to change the WVP. Regarding the calorimetric analyses, the samples presented yellow shades derived from the CHI. The presence of PCL increased opacity of the samples when compared to the CHI film, due to the formation of a crystalline phase, observed in XRD analysis. Thus, the formation of crystals increased light reflection. The blends presented higher flexibility and lower water solubility with the reduction of up to 36% and 26% for the Young modulus and solubility, respectively. According to the results, the blends can be applied as an alternative to commercial non-biodegradable polymers, such as Low Density Polyethylene (LDPE), in the application of food packaging for dehydrated products.